Quof work life (QWL) in terms of Organizational culture on employees at PT. Bank Mayapada International, Tbk Medan City - Agus Halim (Jurnal Psikologi Universitas HKBP Nommensen, 2019)
This study aim to examine the relationship between organizational culture and quality of work life. Subjects of this study are employees at PT. Bank Mayapada International, Tbk as many as 109 people using total sampling method. Data are obtained from scale to measure organizational culture and quality of work life. The calculation is performed through the analysis prerequisite test (assumption test) that consists of normality test of distribution and linearity test of relationship. Data analysis used is Product Moment correlation through SPSS 17 for Windows. Result of this study show a correlation coefficient of 0.704 with p 0.000 (p < 0.05). It shows there is a positive relationship between organizational culture and quality of work life. Organizational culture is one of the factors that affect quality of work life with contribution of (R2) 49.6 percent and the remaining of 50.4 percent is affected by other factors not examined. In conclusion, the hypothesis of there is a positive relationship between organizational culture and quality of work life can be accepted.